Lexical Processes and Eye Movements in Neglect Dyslexia - Giuseppe di Pellegrino; Elisabetta Làdavas; Claudio Galletti (Behavioural Neurology)
Neglect dyslexia is a disturbance in the allocation of spatial attention over a letter string following unilateral brain damage. Patients with this condition may fail to read letters on the contralesional side of an orthographic string. In some of these cases, reading is better with words than with non-words. This word superiority effect has received a variety of explanations that differ, among other things, with regard to the spatial distribution of attention across the letter string during reading. The primary goal of the present study was to explore the interaction between attention and lexical processes by recording eye movements in a patient (F.C.) with severe left neglect dyslexia who was required to read isolated word and non-word stimuli of various length.